Definition of secret reasons of errors, appeared during aviation operators’ professional activity - Луппо, O.Є.; Алєксєєв, О.М. (Proceedings of National Aviation University (archive), 2005)
Development of discover secret reasons of error actions of aviation operators allows to define reasons of secret factors of error action in time and will give opportunity to develop more effective prevention measures in order to prevent mistake actions in time.